1999
DOI: 10.1161/01.atv.19.4.996
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Gradient in Shear But Not Steady Shear Stress Induces PDGF-A and MCP-1 Expression in Endothelial Cells

Abstract: Abstract-Three well-defined laminar flow profiles were created to distinguish the influence of a gradient in shear and steady shear on platelet-derived growth factor A (PDGF-A) and monocyte chemoattractant protein-1 (MCP-1) expression in human endothelial cells. The flow profiles (16 dyne/cm 2 maximum shear stress) were ramp flow (shear stress smoothly transited at flow onset), step flow (shear stress abruptly applied at flow onset), and impulse flow (shear stress abruptly applied for 3 s only). Ramp flow indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
121
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(131 citation statements)
references
References 59 publications
9
121
0
Order By: Relevance
“…2 These changes in gene expression result from modulation of either the production or the activity of transcription factors. [32][33][34] By stably overexpressing LKLF in cultured endothelial cells we now show that a distinct group of known shear-stress regulated genes involved in controlling vascular tone, ACE, EDN, ADM, and NOS3, can be transcriptionally regulated by LKLF. Furthermore, knockdown of LKLF using RNA interference revealed that the response of these genes to flow is primarily dependent on LKLF, with the exception of ACE.…”
Section: Discussionmentioning
confidence: 75%
“…2 These changes in gene expression result from modulation of either the production or the activity of transcription factors. [32][33][34] By stably overexpressing LKLF in cultured endothelial cells we now show that a distinct group of known shear-stress regulated genes involved in controlling vascular tone, ACE, EDN, ADM, and NOS3, can be transcriptionally regulated by LKLF. Furthermore, knockdown of LKLF using RNA interference revealed that the response of these genes to flow is primarily dependent on LKLF, with the exception of ACE.…”
Section: Discussionmentioning
confidence: 75%
“…While human in vivo studies typically describe shear stress as a mean construct, numerous secondary phenomena associated with flow, including pulsatile flow, retrograde flow, and flow turbulence, can influence the regulation of endothelial cells [67][68][69][70][71][72] .…”
Section: Importance Of the Velocity Profilementioning
confidence: 99%
“…In vitro studies suggest that these two distinct fluid stimuli (velocity acceleration vs. steady shear) regulate short-and longterm endothelial function via independent biomechanical pathways 70,71,[73][74][75] . Studies have shown that the rate of velocity acceleration can affect the progression of atherosclerosis 70,73,76) , endothelial cell function 71 , 74) , mechanotransduction 77,78) , calcium kinetics 79,80) , and vascular tone 81,82) . Conditions which affect velocity acceleration include ventricular ischemia 83) , acute myocardial infarction 84) , stenosis 85) , hypertension 86) , and hyperthyroidism 87) .…”
Section: Velocity Acceleration and Endothelial Functionmentioning
confidence: 99%
“…6). In vitro studies suggest that these two distinct fluid stimuli (velocity acceleration vs. steady shear) regulate short-and long-term endothelial function via independent biomechanical pathways (Ojha 1994;Bao & Lu et al 1999;White & Haidekker et al 2001;Hsiai & Cho et al 2002DePaola, 1992 (Ojha 1994;Bao & Lu et al 1999;Hsiai & Cho et al 2001), endothelial cell function (White & Haidekker et al 2001 ;Hsiai & Cho et al 2002), mechanotransduction (Hsieh & Li et al 1993;Bao & Clark et al 2000), calcium kinetics (Helmlinger & Berk et al 1995;Blackman & Barbee et al 2000), and vascular tone (Frangos & Eskin et al 1985;Noris & Morigi et al 1995 ). Conditions which affect velocity acceleration include ventricular ischemia (Sabbah & Przybylski et al 1987), acute myocardial infarction (Kezdi & Stanley et al 1969), stenosis (Bassini & Gatti et al 1982), hypertension (Sainz & Cabau et al 1995), and hyperthyroidism (Chemla & Levenson et al 1990).…”
Section: Velocity Acceleration and Endothelial Functionmentioning
confidence: 99%